Pengembangan Media Bahasa Arab Menggunakan Web Educandy - Fina Nur Fadhilah (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2022)
Faced with the covid-19 pandemic, the media becomes a transformation of the changing conditions of teaching and learning activities, so that an educator is required to be able to adjust the learning process by using online media as a learning innovation. The innovation effort is in the form of educandy game-based learning media with the aim of increasing student motivation and encouraging students to play an active role in learning Arabic. This research is a development research that uses research methods R&D proposed by Borg and Gall which researchers limit only 7 steps, namely: 1) problem identification; 2) data collection; 3) product design; 4) design validation; 5) product trials; 6) product revision; 7) Test usage. The result of this study is that educandy media deserves to be used as a medium for evaluation of arabic language learning at the elementary school level. The use of educandy web media also received a "positive" response from 40 students of grade IV Muhammadiyah Bandongan Elementary School in Magelang with a percentage of 92.5% showing interest and motivation to learn Arabic students increased, and as much as 85% showed that students' Arabic vocabulary mastery increased.